2007
DOI: 10.1086/522374
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Based Approaches for Analysis of Genomewide Association Studies

Abstract: Published genomewide association (GWA) studies typically analyze and report single-nucleotide polymorphisms (SNPs) and their neighboring genes with the strongest evidence of association (the "most-significant SNPs/genes" approach), while paying little attention to the rest. Borrowing ideas from microarray data analysis, we demonstrate that pathway-based approaches, which jointly consider multiple contributing factors in the same pathway, might complement the most-significant SNPs/genes approach and provide add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,020
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(1,035 citation statements)
references
References 29 publications
13
1,020
0
2
Order By: Relevance
“…On the other hand, SNP based GWAS do not identify all disease risk variants. Many variants conferring a small risk are overlooked and many SNPs falling below the accepted threshold of statistical significance may be relevant when investigated through pathway analyses [43,44]. Another limitation is that not all phenotypes were available in both cohorts, which in the case of the TBS data, introduces some uncertainty as to what extent bone microarchitecture rather than bone density is influenced.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SNP based GWAS do not identify all disease risk variants. Many variants conferring a small risk are overlooked and many SNPs falling below the accepted threshold of statistical significance may be relevant when investigated through pathway analyses [43,44]. Another limitation is that not all phenotypes were available in both cohorts, which in the case of the TBS data, introduces some uncertainty as to what extent bone microarchitecture rather than bone density is influenced.…”
Section: Discussionmentioning
confidence: 99%
“…increasing the numbers of study participants, collaborative studies and leveraging high-density genomic data using techniques such as imputation 135 and pathway snP analysis [136][137][138][139] will help to accelerate data acquisition to find precise candidate regions or vur-specific genes. Genomic copy-number variation (Cnv) has been shown to be an important pathogenic mechanism in many other disorders in recent years, 140 but no Cnv study in vur has been reported to date.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…However, this is not to say that useful information about disease pathophysiology cannot be attained through analytic approaches that fall short of identifying a comprehensive catalogueue of individual risk variants. Thus, it has been argued that useful insights into complex disorders can be provided by analyses in which evidence is accrued for association at the gene-wide level 9,10 or at the level of pathways derived from sets of genes 11,12 that are in some way functionally interconnected. Rather than focussing on individual SNPs, the analytic approach is based on extracting information from multiple SNPs within genes or within pathways and testing whether en masse, there is some significant excess of association signal in those genes or pathways.…”
Section: Introductionmentioning
confidence: 99%